Performance of ZnSe(Te) as fiberoptic dosimetry detector. (October 2016) - Ramírez, M.; Martínez, N.; Marcazzó, J.; Molina, P.; Feld, D.; Santiago, M.
Abstract: Fiberoptic dosimetry (FOD) is an experimental technique suitable for in-vivo, real time dosimetry in radiotherapy treatments. FOD relies on using a small scintillator coupled to one end of a long optical fiber. The scintillator is placed at the point where the dose rate is to be determined whereas a light detector at the other end of the fiber measures the intensity of the radioluminescence emitted by the scintillator. One of the problems hampering the straightforward application of this technique in clinics is the presence of Cherenkov radiation generated in the fiber by the ionizing radiation, which adds to the scintillating light and introduces a bias in the dose measurement. Since Cherenkov radiation is more important in short wavelength range of the visible spectrum, using red-emitting scintillators as FOD detectors permits to reduce the Cherenkov contribution by using optical filters. In this work, the performance of red-emitting tellurium-doped zinc selenide crystal as FOD detector is evaluated and compared to the response of an ion-chamber. Highlights: Red-emitting ZnSe(Te) scintillator as fiberoptic dosimetry detector is investigated. Stems effect can be efficiently reduced by optical filtering. ZnSe(Te)-based dosimetry probes are suitable for small-field dosimetry in LINAC.